Analysis and Realization of Card Flicking Manipulation Using a High-Speed Robot Hand. (23rd September 2015) - Yamakawa, Yuji; Namiki, Akio; Ishikawa, Masatoshi
In this study we successfully demonstrated a dexterous manipulation of sheet-like elastic objects — namely playing cards — using a high-speed multifingered robot hand system. Our goal in this research was to achieve card flicking by vibrating a fingertip of the robot hand at high speed. Firstly, we discuss card grasping in the initial state based on the geometrical conditions of the card and the kinematics of the robot hand. Secondly, we propose a strategy for performing the card flicking. In addition, we obtain the card-flicking conditions by analysing the slip between the card and the fingertip of the robot hand. In addition, we analyse an energy transition of the card based on the physical law. Thirdly, we estimate a spring constant of the card via a vibrational experiment. Then we simulate the trajectory of a flying card after the slippage, and compare a simulation result with an experimental result of the flying card's trajectory. Finally, we show the experimental results of card flicking using the high-speed robot system and the proposed method.